STRATEGI PENGANGGARAN MODAL UNTUK MENINGKATKAN KEBERLANGSUNGAN UMKM: STUDI KASUS PADA USAHA NANNOS RACING - Aly, Balqiz Syavira; Atarwaman, Rita J D; Loilatu, Alisa; Restiani, Dwi Nova; Banawi, Johan Daud; Mega; Sombalatu, Marsanda; Rahanubun, Natalia T; Lausiry, Permata Sari; Lukaraja, Sindi; Mustamu, Syantal; Poipessy, Sitiria (PT. Jurnal Center Indonesia Publisher, 2025)
Capital budgeting is a crucial aspect of financial management for MSMEs (Micro, Small, and Medium Enterprises) to ensure business sustainability and growth. This study aims to analyze the capital budgeting strategies implemented by Nannos Racing to support their business continuity. The method used is a case study with data collected through direct observation, interviews with the owner, and documentation. The results indicate that well-planned and structured capital budgeting helps Nannos Racing optimize investment fund usage, reduce financial risk, and improve operational efficiency. An appropriate capital budgeting strategy also contributes to better investment decision-making and supports business expansion. This study recommends that MSMEs adopt systematic capital budgeting practices as part of their financial strategies to ensure business.